Evan’s syndrome- unusual presentation: a case report - Gedam, Smruti D.; Fidvi, Juzar I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Evans syndrome is an extremely rare type of autoimmune (hemolytic) disorder due to development of auto-antibodies against own RBCs, platelets and, at-times, neutrophils; most common presentation being mucosal and cutaneous bleeding with varying degree of anemia with thrombocytopenia. The present case is an unusual presentation of Evans syndrome with massive intra-peritoneal bleeding secondary to ruptured ovarian hemorrhagic cyst, which was managed successfully with timely decision of exploratory laparotomy, steroid, immunosuppressant and transfusion with adequate and appropriate blood and blood products. High index of suspicion and multi-disciplinary approach remained the key factors towards a successful outcome and patient went home in good health on 18th post-operative day.